ATTITUDES OF PEDIATRIC NURSES AND TEACHERS TOWARDS CHILDREN'S RIGHTS AND THEIR PARENTAL ATTITUDES - Esra Tural BÜYÜK (Rojan GÜMÜŞ, 2021)
All professional disciplines working with children have important responsibilities for raising healthy generations. Nurses and teachers have responsibilities in the healthy growth and development of children within the family and society in physical, cognitive, emotional, and social aspects. The study aims to determine the attitudes of pediatric nurses and elementary school teachers working in the northern part of Turkey towards children's rights and their parental attitudes. This was a descriptive and cross-sectional study that was completed with a total of 258 individuals including 135 nurses and 123 teachers. 'Personal Information Form', "Children's Rights Attitude Scale (CRAS)" and "Parental Attitude Scale (PAS)" were used to evaluate sociodemographic characteristics of the nurses and teachers and their parental attitudes and attitudes towards children's rights. The data obtained from the study were analyzed by SPSS 21.0 program. Of the individuals who participated, 52.1% were nurses and 47.9% were teachers. It was found that the mean CRAS score was 37.8±9 for nurses and 31.4±9 for teachers. A statistically significant difference was found between the mean CRAS scores of the nurses and teachers (p˂0.05). The mean PAS score was 22.0±5 for nurses and 18.8±5 for teachers, and a statistically significant difference was found between them (p˂0.05). In the correlation studies between mean CRAS and PAS scores of the nurses and teachers, mean CRAS scores were found to be negatively correlated with PAS-democratic attitude. It was found that nurses and teachers showed positive attitudes towards children's rights, most of them did not get any training on this subject, and nurses who took education on children's rights exhibited more positive attitudes. It was also found out the attitudes of the nurses and teachers, who thought that children's rights were violated, were more positive.